Local house price effects of internal migration in Queensland: Australia's new interstate migration capital - Isil Erol; Umut Unal (Philipps-University Marburg, School of Business and Economics, 2021)
This paper examines the causal impact of internal migration on house price changes in Queensland - Australia's new capital of interstate migration. We study annual housing price growth across 82 Statistical Areas Level 3 (SA3) regions between 2014 and 2019 by employing a spatial correlation approach. We also estimate the impact of the increasing share of migrants from New South Wales on the local housing markets in Queensland. The main findings are summarised as follows: (1) an annual increase in the inflow of migrants equal to 1% of a region's initial population leads to a 0.6-0.7% annual increase in Queensland's house prices across different empirical specifications; (2) internal migration inflow increases house prices in Greater Brisbane metropolitan area, whereas internal migration has a negative impact on housing price changes in the Rest of State regions; (3) migrants tend to move towards SA3 regions where house prices grow more slowly conditional on the local area controls and the time fixed effects; (4) the increasing share of migration from New South Wales does not have a significant effect on house price growth in Queensland. Our findings have important policy implications related to sustainable local economic development since sustainable development is, for the most part, achieved by attracting newcomers to the cities/towns and completed through the involvement of migrants in local housing and labour markets.
Keywords: R12; R23; R31; 330; Housing prices; Internal Migration; Shift-share instrument; Australia; Queensland